About modeling of working process of ship diesel at use as fuel of gas condensate from Urengoy fields - A. V. Shtib; V. R. Vedruchenko; I. I. Malahov (Омский научный вестник)
The article provides a brief overview of the basic physical and chemical properties of different fuels including mixtures of diesel fuel and gas condensate. The analysis of indicators of working process of the diesel engine on liquid fuel of different structure is considered. Graphical and analytical interpretation of the operating cycle, fuel combustion and pressure changes are presented. The influence of the properties of liquid standard and alternative fuels on the parameters of the working process is analyzed. The results of numerical simulation of the diesel indicator process on a mixture of gas condensate and standard diesel fuel are analyzed.